2022
DOI: 10.1002/jha2.461
|View full text |Cite
|
Sign up to set email alerts
|

Two ophthalmic presentations of chronic myeloid leukaemia

Abstract: Chronic myeloid leukaemia (CML) is a myeloproliferative neoplasm that accounts for 15% of newly diagnosed cases of leukaemia in adults [1]. In the developed world, 50% of patients are asymptomatic at diagnosis with the disease picked up on routine examination and blood testing. At presentation, 90%-95% of patients have chronic phase CML during which signs and symptoms typically result from anaemia and splenomegaly [2]. Ophthalmic presentations of CML are uncommon, F I G U R E 1 (A and B) Right and left wide-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Ophthalmic presentation of CML is a rare event. A recent literature review found 40 published cases in the preceding 49 years 1 and at least seven further cases have subsequently been reported 2–6 . The median WBC count amongst patients with ophthalmologic involvement was 249 × 10 9 /L (range 50–688 × 10 9 /L).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ophthalmic presentation of CML is a rare event. A recent literature review found 40 published cases in the preceding 49 years 1 and at least seven further cases have subsequently been reported 2–6 . The median WBC count amongst patients with ophthalmologic involvement was 249 × 10 9 /L (range 50–688 × 10 9 /L).…”
mentioning
confidence: 99%
“…A recent literature review found 40 published cases in the preceding 49 years 1 and at least seven further cases have subsequently been reported. [2][3][4][5][6] The median WBC count amongst patients with ophthalmologic involvement was 249 Â 10 9 /L (range 50-688 Â 10 9 /L). There was a male preponderance with an age range of 9-68 years (median 35 years).…”
mentioning
confidence: 99%